A novel tetravalent Leptospira bacterin protects against infection and shedding following challenge in dogs. (16th February 2013) - Klaasen, H. L. B. M.; van der Veen, M.; Molkenboer, M. J. C. H.; Sutton, D.
Abstract : Recent evidence based on the current epidemiological situation suggests that vaccines against canine leptospirosis in Europe should be directed against infection with Leptospira interrogans ( sensu lato ) serogroups Canicola, Icterohaemorrhagiae, Grippotyphosa and Australis. In the eight studies presented here, dogs were vaccinated with Nobivac L4 (MSD Animal Health), a new tetravalent inactivated vaccine containing antigen from four strains representing these four serogroups. The dogs were then challenged, together with unvaccinated control dogs, using heterologous strains from the same four serogroups. In four of the studies, pups without agglutinating antibodies against the four serogroups were vaccinated with Nobivac L4 vaccine. In a further four studies, Nobivac L4 vaccine was given 48 hours after administration of antiserum from vaccinated dogs designed to mimic the serological status of pups with maternally derived antibodies against these serogroups. In all eight studies, vaccine efficacy was assessed in terms of antibody response, clinical signs, fever, thrombocyte count, frequency of positive isolation of challenge organisms from blood, urine and kidney and frequency of interstitial nephritis. The results demonstrate that Nobivac L4 vaccine induces sterile immunity against leptospiraemia and renal infection with strains of serogroups Canicola, Icterohaemorrhagiae and Grippotyphosa, and induces sterile immunity against leptospiraemia with a strain of serogroup Australis. Since sterile immunity was achieved in pups pretreated with antiserum as well, it can be concluded that this vaccine is also likely to be efficacious in the face of maternally derived antibodies in pups from the age of six weeks.